PRINTED CIRCUIT BOARD FABRICATION WITH EAGLE LIGHT - Soon Chin Fhong; Ignatius Agung Wibowo (2009)
Printed Circuit Board Making Using Eagle was initiated with the intention to help the undergraduate student to possess a skill in fabricating printed circuit board for their graduation project through a CAD tool known as Eagle. Indeed, the skill requirement is not just restricted to undergraduate students, all technical school and college students who are doing an electronic or electrical course must have the experience in producing a printed circuit board. This book is also written to meet the needs of the electronic hobbyist, perhaps, are interested to overcome the complexity problem in electronic design by using Eagle as a tool. A major portion of this book is practically oriented, and it has been carefully written in such a way that step by step guidance is provided to straighten the learning path. Follow the instructions of the book should enable you to acquire the skill in creating a useful printed circuit board with Eagle. It makes your acquisition of a CAD tool skill so much easier at the end of the day.